Context specificity in the assessment of psychosocial risk at work: an empirical study on Italian call centre workers / Specificità di contenuto nella valutazione del rischio lavorativo psicosociale: studio empirico sui lavoratori italiani di call centre - Camerino, Donatella; Conway, Paul Maurice; Fattori, Alice; Cassitto, Maria Grazia; Punzi, Silvia; Fichera, Giuseppe Paolo; Menoni, Olga; Campanini, Paolo (La Medicina del Lavoro, 2014)
SUMMARY Background: Following EU requirements, in recent years standard procedures for the assessment of workrelated stress have been developed in Italy. However, while such standardization has facilitated the spread and use of these procedures, it has brought a lack of specificity in risk assessment. Objectives: To exemplify a method for the assessment of workrelated stress that was developed by the University of Milan to allow the definition of risk profiles tailored to the different organizational settings. Methods: We examined risk factors for workrelated stress in call centre operators employed by two separate Italian companies. At an early stage of the assessment procedure, we conducted a wide series of consultation and training activities that allowed the identification of contextspecific risk factors and homogeneous groups, which fuelled the preparation of both the “objective” and the “subjective” evaluation instruments. Results: Results obtained by means of the standardized “EffortReward Imbalance Questionnaire“ and “Job Content Questionnaire”, interpreted in the light of consultations with key organizational figures and individual interviews with employees, have allowed the detection of different risk profiles and priorities for intervention at both the group and the organizational levels. Conclusions: Findings demonstrated the existence of both common and specific risk factors in the two companies, which would have remained undetected with the exclusive use of standardized approaches. RIASSUNTO «Specificità di contenuto nella valutazione del rischio lavorativo psicosociale: studio empirico sui lavoratori italiani di call centre. Introduzione: Seguendo modelli europei di buone prassi, in Italia sono stati proposte delle procedure standard di valutazione dello stress lavorocorrelato che hanno facilitato una loro diffusione ed applicazione a scapito, tuttavia, di una buona specificità. Obiettivi: Con questo studio ci si è proposti di esemplificare il metodo con cui l’Università degli Studi di Milano affronta la valutazione dei problemi “stress – lavoro correlato” al fine di offrire risposte mirate alle diverse esigenze di miglioramento. Metodi: La procedura d’indagine di “operatori di call centre” di due diverse aziende ha previsto, fin dalle prime fasi dell’indagine, una consultazione allargata e formazione per consentire una buona individuazione dei rischi, una selezione dei gruppi omogenei, la messa a punto degli strumenti “oggettivi” e soggettivi. Risultati: I risultati delle scale standard “Effort Reward Imbalance” e “Job Content Questionnaire” interpretati alla luce delle consultazioni con le diverse parti per l’area call centre e delle interviste individuali hanno consentito di rilevare differenti priorità e gravità delle situazioni sia a livello di sistema organizzativo che di gruppo di lavoro. Conclusioni: I risultati dimostrano problemi comuni e specificità nelle due diverse aziende non rilevabili con le sole misure standardizzate.